Clinical aspects and factors associated with post-traumatic stress in adult patients from three cities in the Peruvian highlands. - Contreras-Rodríguez, Jimena (2022)
Post-traumatic stress disorder (PTSD) is a psychiatric condition that occurs in response to traumatic events and can significantly affect the patient’s functional capacities. The Peruvian highlands is a region whose population has been exposed to highly stressful events; however, there is limited information on the factors associated with PTSD in the region. Objective: To determine sociodemographic and clinical factors (comorbidity and functionality) associated with PTSD. Material and methods: A secondary study was conducted using the adult database of the Epidemiological Study of Mental Health in the Peruvian Highlands - 2017. Instruments: Mini International Neuropsychiatric Interview (MINI) Spanish version ICD-10, Mental Health Questionnaire of Colombia, Disability Scale, and an intake form with demographic data and poverty indicators. Results: Significant associations were found between PTSD and groups of married people and those who had no school education. Depressive episode was the most frequent comorbidity. The main stressors were political violence and serious accidents. Likewise, there was an association of PTSD with suicidal thinking and difficulties in planning, organizing and executing a variety of activities. Conclusions: PTSD was associated with some sociodemographic factors, traumatic events and clinical disorders. Intervention programs should be aimed at providing immediate care to people exposed to traumatic events and at reducing the presence and impact of such stressors in the Andean region.